Cardiac Involvement in Granulomatosis with Polyangiitis - McGeoch, Lucy (J Rheumatol, 2015)
OBJECTIVE: To determine frequency and outcomes of granulomatosis with polyangiitis (GPA)–related cardiac disease in a North American GPA cohort. METHODS: Analysis was done of all patients in the Vasculitis Clinical Research Consortium Longitudinal Study of GPA. Demographic and clinical characteristics of patients with and without GPA-related cardiac involvement were compared. RESULTS: Of 517 patients with GPA, 3.3% had cardiac involvement. No differences were observed between patients with or without cardiac involvement in terms of demographics, antineutrophil cytoplasmic antibody positivity, or relapse rate. CONCLUSION: Cardiac involvement in GPA is rare and heterogeneous. In this cohort, cardiac involvement was not associated with a higher rate of relapse or premature death.